NOTES ON INDONESIAN FRESHWATER ALGAE III*NEW VARIETIES OF SOME LITTLE-KNOWN STAURASTRA (DESMIDIACEAE) - ARTHUR M. SCOTT; G. W. PRESCOTT (BRIN Publishing (Penerbit BRIN), 1958)
Described and figured are Staurastrum freemanii West & West and var. triquetrum West & West, with two new varieties, var. nudiceps and var. evolutum; also three new i'ormae, var. nudiceps fa. biradiatum, var. triquetrum fa. trispinatum, and var. evolutum fa. trispinatuin. In St. salterns Josh, the specific form was not found, but two new varieties are named, var. polycharax and var. sumatranum, with a fa. divergens of the latter; also two new formae of the species, St. saltans fa. kalimantanum and fa. javanicum. In St. subsaltans West & West, var. indonesianum and fa. diver gens are named as new. Correction. Because of pre-emption the name Euastrum latwm sp. nov. Krieg. & Scott (1957) is changed to E. neolatum Krieg. & Scott.